How Long Should the Prone Position be Applied in the Treatment of SARS-CoV-2 ARDS? - Tuğba Yücel; Sinan Aşar; Canberk Çetinel; Aylin Parmaksız; Yasemin Tekdöş Şeker; Zafer Çukurova (Türk Yoğun Bakim Derneği Dergisi, 2024)

(untitled)
Objective: The importance of prone positioning has increased with the density of coronavirus disease-2019-related acute respiratory distress syndrome (C-ARDS) during the pandemic process. It is aimed to investigate the effect of prolonged duration of prone positioning in C-ARDS patients on the blood gas parameters at the time after supine positioning (post-prone effect), the feasibility, the safety, and the mortality for 28 days. Materials and Methods: This study was a single-center prospective observational study with 1000 beds, 432 of which were intensive care units. Severe and moderate ARDS; the blood gas parameters (PaO2/FiO2, PaO2, SpO2 etc.) of the patients who were applied the standard prone (16 hours) and the extended prone (36 hours) position were compared. Results: It was observed that PaO2/FiO2 PaO2 and SpO2 values measured at the 8th hour (t4) (post-prone) after the prone was placed in the supine position in the prolonged prone group were higher than before the prone (t1) (p<0.001). In the standard prone group, PaO2/FiO2, PaO2, and SpO2 values were not maintained in the post-prone period and were even lower than before the prone. The mortality of patients in the standard prone group was 51.7% (n=31); in the prolonged prone group, the mortality was 45% (n=27). Conclusion: With the application of the prolonged prone position, it has been observed that C-ARDS patients have better blood gas exchange with less manpower without harming the patients (pressure ulcer, retinal damage, joint damage, etc.).